2016
DOI: 10.11114/jets.v4i6.1399
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Physical Performance Status of Visually and Hearing Impaired Applying Judo Training Program

Abstract: It was aimed to investigate the physical performances of visually and hearing impaired doing judo training in this study. 32 male athletes, who were doing judo training, volunteer and, visually and hearing impaired, participated in this study. The investigation was applied to visually impaired (N=12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…These authors concluded that the Balance Error Scoring System test may not be sensitive to group-related differences in the quantitative kinematics of postural control. Eventually, in comparison with other athlete populations, para-judokas showed better postural control than those with hearing impairment 28 …”
Section: Resultsmentioning
confidence: 81%
“…These authors concluded that the Balance Error Scoring System test may not be sensitive to group-related differences in the quantitative kinematics of postural control. Eventually, in comparison with other athlete populations, para-judokas showed better postural control than those with hearing impairment 28 …”
Section: Resultsmentioning
confidence: 81%
“…In our study, isokinetic knee flexion - extension muscular strength at 60°/sec and 240°/sec angular velocity were found similar on both sides in athletes with visual and hearing impairment. Although there were several studies investigating the muscular strength and balance of healthy group and athletes, comparison of muscular strength and balance between athletes with visually and hearing impairment has not been made yet ( Karakoc, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate balance depends on the integration of multisensory system, consisting of the vestibular, visual and somatosensory system and the inadequacy of which negatively impact ( Greve et al, 2013 ). Therefore, it wasn’t surprising that severe hearing and visual loss have been proven to have negative effects on balance and postural adjustment ( Karakoc, 2016a ; Karakoc, 2016b ). Balance is not only an important factor to maintain postural control but achieve healthy body composition and physical fitness to successfully perform sportive activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations